Modern trends in the development of medical instruments and implants using plasma surface modification technologies - Alontseva, D.L.; Azamatov, B.N.; Voinarovych, S.G.; Yersainova, A.V. (Recent Contributions to Physics, 2026)
This review article presents an overview of current trends in the development of medical instruments and implant manufacturing technologies, with an emphasis on digital design, additive manufacturing, and surface engineering methods, and a focus on the use of plasma technologies. The review aims to systematically analyze modern technological approaches and identify key limitations that hinder the widespread implementation of innovative technologies for the production of medical implants in clinical practice. The evolution of manufacturing methods from traditional mechanical processing to personalized and functionally oriented production is considered.  Advances in 3D modeling, 3D printing of metal and polymer structures, plasma and ion-plasma modification of implant surfaces, robotic surgical platforms, and combinations of these advanced technologies are analyzed.  Particular attention is paid to the characteristics of thermal plasma spraying, the patterns of influence of plasma spraying parameters on the microstructure and surface properties of medical devices, as well as the technological limitations of the implementation of combined technologies for the manufacture of medical devices, including the variability of the quality of additive manufacturing, the complexity of material certification, and the lack of unified standards for personalized medical devices. Promising directions for further research and ways to improve the efficiency of innovative plasma technologies implementation for modifying the surface of medical instruments and implants can be identified through the analysis and generalization of contemporary scientific data presented in this review.
Keywords: medical implants, additive manufacturing, plasma technologies, surface modification, biocompatible materials, digital design, thermal plasma spraying (TPS).